The neutrophil-to-lymphocyte ratio makes the Heng risk model improve better the prediction of overall survival in metastatic renal cell cancer patients. (20th July 2018) - Kim, Sung Han; Kwon, Whi-An; Kim, Sohee; Joung, Jae Young; Seo, Ho Kyung; Lee, Kang Hyun; Chung, Jinsoo
Abstract : A novel modification of the Heng risk model includes inflammatory factors, including the neutrophil-to-lymphocyte ratio, to better predict overall survival in patients with metastatic renal cell carcinoma. Abstract: Objective: The aim of this study was to predict the discriminating prognostic power of the neutrophil-to-lymphocyte ratio for overall survival in patients with metastatic renal cell carcinoma and to make a new model using the neutrophil-to-lymphocyte ratio. Methods: From 2007 to 2014, 190 patients with metastatic renal cell carcinoma treated with either systemic immunotherapy or/and vascular endothelial growth factor-targeted therapy were enroled. A multivariable proportional hazard model was developed to investigate the effects of the neutrophil-to-lymphocyte ratio as predictive prognostic factors for overall survival. This new model was incorporated into the current Heng risk model to validate a modified prognostic classification for overall survival. Results: In multivariable analysis, a high neutrophil-to-lymphocyte ratio [hazard ratio (HR) = 1.65] was a significant independent predictor of shorter overall survival ( P = 0.005). Additional neutrophil-to-lymphocyte ratio markers improved the discriminating power of the Heng risk classification, as compared to the existing classification model (C-statistic: 0.7198 vs. 0.6943, P = 0.008). The reclassification of patient prognostic categories using the new model showed a total overall net improvement of 61.4% ( P < 0.001). Conclusion: The neutrophil-to-lymphocyte ratio was a significant prognostic factor of overall survival in metastatic renal cell carcinoma patients treated with systemic therapy. Adding the neutrophil-to-lymphocyte ratio to the Heng model significantly improved the discriminatory power of risk prediction in metastatic renal cell carcinoma.